ANALISIS PEMAHAMAN INFORMASI DAMPAK SEKS BEBAS PADA PESERTA DIDIK SMP NEGERI 1 SIANTAN - Rahmayanti Rahmayanti; Luhur Wicaksono; Yuline Yuline (Universitas Tanjungpura, 2020)
AbstractThis study discusses the analysis of informs services about the impact of free sex on grade VIII students of SMP Negeri 1 Siantan in 2019. The problem in this study is how is the understanding of the impact of free sex on students. The purpose of this study was to obtain objective information about understanding the impact of free sex on students of class VIII of SMP Negeri 1 Siantan in 2019 The method used is descriptive, the type of research used is survey research. The population and sample of this study were a population of 331 and a sample of 35 students. This study uses a quantitative approach. The technique used is not direct communication, this research data collection tool is a questionnaire. The results of this study indicate that the analysis of informs services about the impact of free sex on class VIII students of SMP Negeri 1 Siantan in 2019 viewed from physical, behavioral and psychological, social, economic, religious and legal questionnaires. Based on the description above, it can generally be concluded that the analysis of informs services about the impact of free sex on grade VIII students of SMP Negeri 1 Siantan in 2019 shows very goodKeywords: Sexual impact, information services, free sex